Records of chromatic disorder in Molossus molossus and Sturnira bakeri (Chiroptera) from western Ecuador - Salas, Jaime A. (2021)
Herein we report cases of leucism in Molossus molossus and Sturnira bakeri from three locations of lowlands of western Ecuador, which include three gravid females, five juvenile, four subadult, and six adults. The M. molossus specimens showed white spots on several parts in the soft part of body (ears, tragus, propatagium, uropatagium), and fur (throat, abdomen), while individual of S. bakeri presented a whitish-yellowish patch on its dorsal region, very contrast in yellow-shoulder bats. Although South America has a significant information gap about chromatic disorders in bats, been necessary to continue reporting cases of chromatic disorders to try to determine their causes.